YEREVAN CITY HEAVY METALS POLLUTION INVESTIGATION APPLYING SOIL–PLANT SYSTEM (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
With application of Tradescantia (clon 02) plants test-object was studied the genotoxicity of soil samples’ pollution depending on heavy metals (HM) concentration. At high level of investigating samples pollution by some HM was revealed increase of all studied mutation events frequency in stamen hairs (SH) and the micronuclei in tetrads of microspore (MN) depending on investigating points.
Keywords: heavy metals; Tradescantia (clon 02); micronuclei; mutation events